Book Review African American Readings of Paul: Reception, Resistance and Transformation Lisa M. Bowens Grand Rapids, MI: Eerdmans, 2020 pp 355, hb, ISBN 978-0-8028-7676-8, $40.00. (2021) - Plyming, Philip
No abstract available